MODERN METHODS OF SOWING CEREAL CROPS - BABYN, IHOR; TRUKHANSʹKA, OLENA; BURLAKA, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Analyzing the latest innovations and technological improvements, the article aims to highlight the trends that determine the efficiency and stability of yields in the grain sector. The article examines digital and agricultural technologies that allow agricultural producers to optimize the processes of sowing grain crops. Digital solutions such as data analysis, artificial intelligence and the use of modern agricultural sensors are seen as key tools to improve productivity and optimize resources. Geospatial analysis, taking into account environmental aspects and ensuring sustainable development are also becoming an object of research. The article examines in detail how the use of geographic information systems and the latest ecologically oriented practices can contribute to agriculture that uses resources efficiently and preserves the environment. This article is designed to consider modern methods of sowing grain crops, which define a new stage in the development of the agricultural sector. We will explore innovative strategies, from digital analytics to geospatial solutions, that maximize crop efficiency and promote sustainable use of natural resources. The general emphasis of the article is to highlight promising and practically significant aspects of the use of modern methods of sowing grain crops. The article also considers the challenges that may arise when implementing the latest technologies and provides recommendations for their successful implementation in the agricultural sector.